Analysis of Heat Transfer in Shell and Tube Heat Exchanger (STHE) using Counter and Parallel Flow - Zaidi Mohd Yazid, Muhammad Danial Aiman; Main, Nor Mazlana (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A heat exchanger is a device specifically engineered to enable the transfer of thermal energy between two fluids that have different temperatures. A shell and tube heat exchanger (STHE) is a widely used heat exchanger that facilitates the transfer of heat between a gas or liquid medium. The efficiency of heat exchangers is vital in the thermal industry. The objective of this study is to investigate the efficiency of shell and tube heat exchangers, with a particular focus on parallel and counter flow arrangements when two different fluids are utilized.  Design and simulations are conducted using SolidWorks2020 and computational fluid dynamics (CFD), taking into consideration operational parameters such as flow rates, inlet temperatures, fluid properties, boundary condition and others. The results reveal that counter flow produces a higher temperature difference, improving heat transfer efficiency near the outlet. However, calculated values indicate higher heat transfer in parallel flow, contradicting grapical results which is 86,073.65W for counter flow and 94,975.46W for parallel flow. This discrepancy may stem from various factors. The practical design adheres to Tubular Exchanger Manufacturers Association (TEMA) requirements, providing useful insights into the thermal efficiency of STHE.